Makna Peran Ibu Tunggal pada Video Klip “Nina” Karya Feast - Aliftia Ummi Nofitriasari (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
This study analyzes how the aspirations of a single mother are depicted in the music video "Nina" by Feast. The video portrays the social reality of contemporary women, shedding light on their struggles and aspirations. Using a qualitative approach and Ferdinand de Saussure's semiotics, this research examines the relationship between signifiers and signifieds in both audio-visual and narrative media. The analysis reveals that the aspirations of single mothers are depicted through various symbols, including dialogue and key expressions, which represent the conflict between personal dreams and responsibilities. The music video captures the themes of independence, determination, and sacrifice, as the single mother navigates her roles within society and family. The video emphasizes the internal and external struggles of women as they strive to balance their dreams with the demands of daily life. Ultimately, the study demonstrates how media can reflect and amplify the personal and social dynamics of women, particularly single mothers, in the context of contemporary challenges.